Phase II Study of Preoperative Chemoradiotherapy with Oxaliplatin, Infusional 5‐Fluorouracil, and Cetuximab Followed by Postoperative Docetaxel and Cetuximab in Patients with Adenocarcinoma of the Esophagus: A Trial of the ECOG‐ACRIN Cancer Research Group (E2205). (21st June 2019) - Gibson, Michael K.; Catalano, Paul; Kleinberg, Lawrence R.; Staley, Charles A.; Montgomery, Elizabeth A.; Jimeno, Antonio; Song, Wei (Frank); Mulcahy, Mary F.; Leichman, Lawrence P.; Benson, Al B.
Abstract: Background: A standard approach to treating resectable esophageal adenocarcinoma is chemoradiotherapy (CRT) followed by surgery; however, recurrence is common. To improve this, we designed a single‐arm, phase II trial that added an epidermal growth factor receptor (EGFR) inhibitor, cetuximab (C), to CRT, with the hypothesis that EGFR inhibition would improve pathologic complete response (pCR) rate. Materials and Methods: We aimed to increase the pCR rate from 25% to 45%. A Simon two‐stage design (α and β of 0.10) required pCR/enrolled 5/18 for stage 1 and 14/40 total. CRT: oxaliplatin 85 mg/m 2 days 1, 15, and 29; infusional 5‐fluorouracil 180 mg/m 2 /24 hours × 35 days; C 400 mg/m 2 day 1 then 250 mg/m 2 days 8, 15, 22, and 29 and radiation (intensity modulated radiotherapy [IMRT] allowed) 180 cGy/day × 25 fractions (Monday through Friday). Following esophagectomy, adjuvant chemotherapy (CT): weekly docetaxel 35 mg/m 2 and C 250 mg/m 2 5 out of 6 weeks for two cycles. Results: Of 21 eligible patients enrolled, 17 had surgery; 4 died before operation (due to pulmonary embolism 4 days after CRT, G3 diarrhea, progressive disease during CRT, sepsis/hypoxia during CRT, and acute respiratory distress syndrome [ARDS]). pCR = 7/17. Three postoperative deaths due to ARDS resulted in seven total study‐related deaths. Of the 14 remaining patients, 12 started and completed adjuvant CT. Two of seven patients with pCR died, both of ARDS. Out of the 21 eligible subjects in this study, 13 have died and 8 remain alive. The use of IMRT did not correlate with ARDS. Conclusion: This regimen demonstrated promising activity. Toxicity was significant, with seven study‐related deaths leading to closure after stage 1. All postoperative deaths were due to ARDS. This regimen is not recommended. Abstract : The results of a phase II study evaluating the addition of cetuximab to chemotherapy plus radiation in the treatment of esophageal cancer are presented. Although the regimen demonstrated promising activity, the toxicity was significant, leading to early termination of the study.